Pharmacotherapy of alcohol addiction – new reports - Boreński, Grzegorz; Wójcik, Magdalena; Poleszak, Julita; Szabat, Marta; Szabat, Przemysław; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Alcohol use disorder is a worldwide problem. It can affect people and their families regardless of culture or age. Yet there is still no one good form of treatment. Each patient requires an individual approach. Unfortunately, for some patients current available treatments is not enough. There is a great need for new drugs that could be helpful in treating alcohol use disorder. Here, we integrate the information about the disease itself, current available treatments which is disulfiram, acamprostate and naltrexone and new possibilities in pharmacotherapy. The aim of the study: The purpose of this systemic review was to collect and analyse current and new methods of treatment of alcohol addiction. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: alcohol, treatment, addiction, pharmacotherapy, psychotherapy. Description of the state of knowledge:Currently the basis for alcoholism treatment are psychosocial and behavioral treatments and classic medicines such as disulfiram, acamprostate, naltrexone. New promising off-label medication are baclofen, gabapentin, pregabaline, topiramate, γ‐hydroxybutyrate, nalmefene, ondansetron andvarenicline. The use of these drugs may bring more benefits than use of older medicines. There are numerous studies proving the effectiveness of these drugs. Summary: Therapy for alcohol addiction could be more effective using other medicines than currently. Further research is needed to confirm the effect of new off-label medicines.